Internalisasi nilai-nilai karakter kitab Ta’lim Muta’alim dengan model ‎pembelajaran Project Based Learning di Madin Nurul Huda Karangnongko - Rohmah, Azida Nur (Maliki Interdisciplinary Journal, 2023)
The Book of Ta'lim Muta'allim by Az Zarnuji explains the basic concept of education wrapped in Islamic character values. These character values ​​will lead to success in studying and practicing it. This book is widely studied in non-formal religious education institutions such as madrasah diniah (Madin). Institutions like this mostly use conventional learning models such as lectures, in which the teacher becomes the center of learning. Trying to update the learning model in reviewing this book was carried out using the PjBL (project based learning) model at Madin Nurul Huda Karangnongko. The application of the PjBL (project based learning) modern learning model is carried out with a central focus on students who carry out a learning project to increase students' critical thinking and analytical power in understanding and interpreting the character values ​​contained in this book.